Association of total cholesterol, low‐density lipoprotein cholesterol, and non‐high‐density lipoprotein cholesterol with atherosclerotic cardiovascular disease and cancer in a Chinese male population - Guan, Xu‐Min; Wu, Shou‐Ling; Yang, Xiao‐Lei; Han, Xu; Yang, Yi‐Heng; Li, Xin‐Tao; Bin Waleed, Khalid; Yue Du; Zhan, Si‐Yan; Liu, Ying; Li, Hui‐Hua; Xia, Yun‐Long (International journal of cancer, 2018)
This prospective study included 68,759 Chinese male adults from Kailuan cohort of China who had a standardized medical examination between 2006 and 2007 and were followed up for approximately 8 years until occurrence of ASCVD, cancer or death or until December 31, 2014. Subjects were divided into four categories based on the quartiles of TC, LDL‐C and non‐HDL‐C. Cox regression models were used to estimate hazard ratios (HRs) and their 95% confidence intervals (CIs). During follow‐up, 2,916 males developed ASCVD and 1,884 developed cancer. Compared with the lowest quartile, the upper‐most quartiles of TC, LDL‐C and non‐HDL‐C were all associated with increased ASCVD risk (HR 1.53; HR 1.16; HR 1.55); however, the upper‐most quartiles of TC, LDL‐C and non‐HDL‐C were all negatively associated with cancer (HR0.84; HR 0.82; HR 0.80) and these associations were present after exclusion of incident cancers during the first 4 years of follow‐up. In a word, we report that high TC, LDL‐C and non‐HDL‐C concentrations increased ASCVD incidence in a male population and that these lipid profiles were inversely associated with total cancer and several individual cancers. What's new? High cholesterol is a major risk factor for cardiovascular disease, a leading cause of death worldwide. Cardiovascular disease is potentially associated with cancer, yet despite the common occurrence of both conditions, little is known about their relationship. In this prospective study of more than 68,700 Chinese men, high total cholesterol (TC), high low‐density lipoprotein cholesterol (LDL‐C) and non‐high‐density lipoprotein cholesterol (non‐HDL‐C) concentrations were linked to increased incidence of cardiovascular disease but not cancer. Moreover, the upper‐most quartiles of TC, LDL‐C and non‐HDL‐C levels were negatively correlated with total cancer risk and risk of individual cancers, suggesting an inverse association.